Bee pollen extract of Malaysian stingless bee enhances the effect of cisplatin on breast cancer cell lines - Wan Omar, Wan Adnan; Azhar, Nur Asna; Fadzilah, Nurdianah Harif; Nik Mohamed Kamal, Nik Nur Syazni (Elsevier, 2016)
Objective: To evaluate the antioxidant and antiproliferative effect of methanolic bee pollen extract (BPE) of Malaysian stingless bee [Lepidotrigona terminata (L. terminata)] and its synergistic effect with cisplatin (a chemotherapeutic drug) on MCF-7 cancer cell line. Methods: The antioxidant activity of BPE from L. terminata was measured by using 1,1-diphenyl-2-picrylhydrazyl radical (DPPH) assay. Antiproliferative activity at different concentrations of BPE and cisplatin was determined through using MTT assay on MCF-7 and L929 cell lines. An interaction effect (synergistic, additive and antagonistic) between BPE and cisplatin was determined by CompuSyn software based on MTT assay data. Results: The EC50 (50% decrement of DPPH inhibition) of BPE was 0.5 mg/mL. L. terminata BPE exhibited antiproliferative activity on both cancer and normal cell lines. The IC50 (concentration of drug that was required for 50% of cell inhibition in vitro) of BPE on MCF-7 was 15 mg/mL whereas in normal cell line L929 was 26 mg/mL. The IC50 for cisplatin on MCF-7 was 20 μmol/L. The combination effect of BPE and cisplatin on MCF-7 cells showed that BPE at 15 mg/mL was able to potentiate the inhibitory effect of cisplatin at all different concentrations (2.5–20.0 mg/mL). The average of cancer cells inhibition which was potentiated by BPE was around 50%. A combination index values of less than 1 reported in the CompuSyn software further proved the synergistic effect between BPE and cisplatin, suggesting that BPE was working synergistically with cisplatin. Conclusions: Our study therefore suggested that BPE of Malaysian stingless bee, L. terminata is a potential chemopreventive agent and can be used as a supplementary treatment for chemotherapy drugs. BPE might be able to be used to potentiate the effect of chemotherapy drugs with the possibility to reduce the required dose of the drugs. The molecular mechanisms of how the BPE exerts antiproliferative activity will be a much interesting area to look for in future studies.